2016
DOI: 10.1074/jbc.m116.738518
|View full text |Cite
|
Sign up to set email alerts
|

Bone-protective Functions of Netrin 1 Protein

Abstract: Edited by Amanda FosangNetrin 1 was initially identified as an axon guidance factor, and recent studies indicate that it inhibits chemokine-directed monocyte migration. Despite its importance as a neuroimmune guidance cue, the role of netrin 1 in osteoclasts is largely unknown. Here we detected high netrin 1 levels in the synovial fluid of rheumatoid arthritis patients. Netrin 1 is potently expressed in osteoblasts and synovial fibroblasts, and IL-17 robustly enhances netrin 1 expression in these cells. The bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 53 publications
2
34
0
Order By: Relevance
“…Netrin-1 is a neuroimmune guidance cue. It can inhibit the migration of macrophages, which means that it is an inflammatory factor3536. This can explain the reduced transwell rate of RAW 264.7 cell by polyethylene debris in our study.…”
Section: Discussionmentioning
confidence: 50%
“…Netrin-1 is a neuroimmune guidance cue. It can inhibit the migration of macrophages, which means that it is an inflammatory factor3536. This can explain the reduced transwell rate of RAW 264.7 cell by polyethylene debris in our study.…”
Section: Discussionmentioning
confidence: 50%
“…In addition to the regulation of immune cell migration, Netrin‐1 was shown to regulate the inflammatory response of macrophages through suppression of COX‐2–mediated PGE2 production and also promote macrophage reprogramming to induce inflammation resolution . Furthermore, Netrin‐1 binding with its receptor Unc5b takes part in osteoclast biology and thus suggested as a therapeutic target for inflammatory bone destructive diseases . In this study, Netrin‐1 and its receptor Unc5b were detected in all samples.…”
Section: Discussionmentioning
confidence: 56%
“…In addition to the anti‐inflammatory properties, Netrin‐1/Unc5b interaction takes apart in bone destructive diseases impacting through osteoclast fusion. Blockade of Netrin‐1/Unc5b axis has been shown to prevent bone destruction .…”
Section: Introductionmentioning
confidence: 99%
“…Mediero et al demonstrated that Ntn1, which is produced by osteoclasts enhanced osteoclast differentiation by an autocrine/paracrine manner and Ntn1 deficient mice have markedly diminished osteoclasts, as well as increased cortical and trabecular bone density and volume compared to wildtype mice, suggesting that Ntn1 is a negative regulator in bone metabolism (11). In contrast, Maruyama et al reported that Ntn1 suppresses osteoclast multinucleation, but not osteoclast differentiation and protected the mice against autoimmune bone destruction in vivo, indicating that Ntn1 is a positive regulator in bone metabolism (12). These researchers reported that Ntn1 does not affect osteoblast differentiation.…”
Section: Discussionmentioning
confidence: 94%
“…Among these netrins, netrin-1 (Ntn1) has involved in cytoskeleton reorganization and in epithelial cell adhesion and migration in lung, mammary gland, and pancreas (8-10). Recent studies showed that Ntn1 plays a crucial role in osteoclast differentiation (11,12). As the function of osteoclasts is regulated by Ntn1, the question whether Ntn1 affects cellular function in osteoblasts has been raised.…”
mentioning
confidence: 99%